Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Produk Lung.eraa - Salma, Alisa Rania (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze “The Influence of Product Quality and Service Quality on Purchase Decisions of Lung.eraa Products (A Case Study on the Lung.eraa Shopee E-commerce Store in Surabaya)”, in line with the core issue raised, namely the effect of product quality and service quality on consumer purchase interest in the Lung.eraa online shop business based in Surabaya. High product quality is expected to enhance customer satisfaction, while optimal service quality is expected to build customer loyalty and attract purchase interest. The research method employed is a survey by distributing questionnaires to 100 respondents who are online consumers of Lung.eraa. Data analysis was conducted using multiple linear regression to test the proposed hypotheses. The results of the analysis indicate that product quality has a positive and significant effect on purchase decisions, meaning that the better the product quality offered, the higher the consumer’s intention to purchase. Furthermore, service quality also has a positive and significant influence on purchase interest, indicating that good service can effectively attract consumers. This study contributes to the development of marketing strategies for online business actors to increase purchase decisions by improving product and service quality. Therefore, the recommendation is to continuously enhance both aspects in order to maintain and expand market share within the e-commerce industry.